Utilization of Google Maps as a Medium for Verifying IMB Building Area to Support Accurate Determination of Land and Building Tax (PBB) at the Surabaya City Revenue Agency - Cholid Fadil (Nanggroe: Jurnal Pengabdian Cendikia, 2026)
Google Maps has proven to be an effective digital solution for the initial verification of Land and Building Tax (PBB) data at the Surabaya City Revenue Agency (Bapenda), replacing costly and time-consuming physical survey methods. Out of a total of 413 objects examined, significant discrepancies were found between administrative data (IMB) and actual field conditions. Although the majority (87.65%) of objects matched their recorded existence, 183 objects (44.31%) had building areas that did not correspond with the IMB, with differences of ? 50 m². These findings also include objects that could not be located (11.14%) or were inaccessible (1.21%). Overall, Google Maps successfully accelerated the data screening process and helped officers focus on problematic objects, highlighting the urgency of updating data to ensure more accurate and fair PBB assessments, while also reducing potential regional revenue losses.